Change of the structural organization of erythrocytes at sportsmen which train on endurance - Korzh, V. P. (Morphologija, 2009)
Abstract The quantitative and qualitative adjectives of erythrocytes were studied in 25 athletes of triathlon and biathlon during long physical loads. The activity of G-6-PDG and GR in erythrocytes was studied. The amount and morphological form of erythrocytes changes during adaptation to significant physical loadings. The activities of G-6-PDG and GR reduced. The quantity of G-SH decreased. These shifts were less expressed at good adaptation and it is possible to use them as criterion of a degree of a high class athletes adaptation.